(untitled) (Applied Biological Research, 2019)
The physical fitness index measures the physical fitness for muscular work and he ability to recover from the work. The study was undertaken to assess the physical fitness index and aerobic capacity by using Harvard step test and evaluate hemoglobin level of moderately anemic (8-10.9 mg dL-1) adolescent girls (10-18 yr). Intervention was given 90 moderately anemic adolescent girls divided into three groups for a period of 4 months. Each group constituted 30 girls. Group-I was given iron-rich diet as well as nutrition counseling and group-II received only nutrition counseling. Group-III formed the control group i.e. no intervention of any type was provided to them. The scores of physical fitness index showed the positive impact of intervention on experimental groups. Nutrition intervention improved their physical fitness index and Vo2 max scores level to good and excellent fitness. Nutrition and dietary intervention improved their Hb level. The study concluded that physical fitness index, VO2 max scores and level of hemoglobin improved with diet as well as nutrition counseling nutritional intervention.